(untitled) (Texas Journal of Medical Science, 2023)
Today, the interest in natural medicines has increased significantly in the world. For example, in Germany, 80% of doctors of all specialties regularly use plants in their practice, more than 80% of patients in all countries of the world have been treated with phytopreparations at least once. Therefore, the inventory of common medicinal plants, registration of their reserves, and the search for ways of their sustainable use is a very urgent problem. For this purpose, the medicinal properties and chemical composition of dalchoi (huperisum perforatum l.) cultivated in the conditions of Samarkand region were studied